EFEKTIVITAS KOMBINASI LATIHAN OTOT DASAR PANGGUL DAN PERUT TERHADAP INVOLUSIO UTERI PADA IBU NIFAS - Ulfah, Mariah; Safitri, Maya (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2016)
Maternal Mortality in Banyumas was 114.7 per 100,000 live births, this number decreased when compared to the year 2013 is 126 / 100,000 live births. The direct causes of maternal death are haemorrhage highest 14 cases and 5 cases of eclampsia. Bleeding is due to muscle contractions of the uterus inadequate. Abdominal muscles and pelvic floor muscles is a proponent of uterine muscle. Without these muscles, the muscles of the uterus will be weak and benefit return the tone of the muscles of the pelvic floor that would restore muscle tone was good during the puerperium, so the involution of the uterus will go well. The results showed statistically t: 3.779, p value of 0.000 means that there are significant differences in the average decrease in height between any combination fundus abdominal muscle exercises and pelvic floor muscle exercises with postpartum mothers who are only trained in pelvic floor muscles only. The average decrease in height fundus on a combination of abdominal and pelvic muscle exercises 2:31 cm whereas only do pelvic floor muscle exercises alone is 1.4 cm. There is a significant difference in the average decrease in height between any combination fundus abdominal muscle exercises and pelvic floor muscle exercises with postpartum mothers who are only trained in pelvic floor muscles only. Keywords: Involusio uterine muscle training during childbirth